The response of oil market to US monetary policy surprises. (2018) - Chebbi, Tarek
The impact of monetary policy surprises from the USA on volatility of oil returns are examined over a period of instability from January 5, 2004 through December 31, 2008. Following Kuttner (2001), I use the change in the one-day current-month futures rate at a given date to measure monetary policy news. Using EGARCH model, my results suggest that these shocks are an important driver of the oil market. I find that the volatility reacts in a statistically significant and economically relevant fashion to surprise changes in the target rate. The estimated effect on the volatility is positive. Moreover, I show that the daily changes in federal funds futures rates don't have any role in the dynamics of oil volatility during the sample period. Finally, I also show that all model parameters to be highly significant with higher volatility persistence.